The Effect of Foot Massage with Oil Aromatherapy on Hemodialysis Patients' Sleep Quality - Christine Handayani Siburian; Nataria Yanti Silaban (Universitas Aisyah Pringsewu, 2023)
Hemodialysis is a process of cleaning the blood outside the body that involves taking blood from a blood vessel with a dialyzer. Patients undergoing hemodialysis often experience a decrease in the quality of their sleep. Sleep quality can be improved by taking non-pharmacological measures, namely foot massage. Foot massage can be felt better with aromatherapy oil. This study aims to identify the effect of foot massage with aromatherapy oil on sleep quality in patients undergoing hemodialysis. This study is a quasi-experimental design with an equivalent control group. The sample is 64 selected using consecutive sampling. Data was collected using The Pittsburgh Sleep Quality Index. Data were analyzed by pair t-test and independent t-test. The results showed that there were differences in sleep quality in the intervention group after the action (t=4.34, p=0.000) and in the control group (t=3.31, p=0.002). The results also showed that there was a difference in sleep quality between the treatment group and the control group of patients undergoing hemodialysis (t=2.096, p=0.04). The conclusion is that there is an effect of foot massage with aromatherapy oil on sleep quality in patients undergoing hemodialysis. Suggestions for a foot massage with aromatherapy can be one of the non-pharmacological measures to help improve sleep quality in patients undergoing hemodialysis. Abstrak: Hemodialisis adalah proses pembersihan darah di luar tubuh yang melibatkan pengambilan darah dari pembuluh darah dengan dialyzer. Pasien yang menjalani hemodialisa sering mengalami penurunan pada kualitas tidurnya. Kualitas tidur dapat mengalami peningkatan dengan dilakukan tindakan non farmakologi yaitu foot massage. Foot massage dapat lebih dirasakan dengan adanya aromatherapy oil. Penelitian bertujuan untuk mengidentifikasi pengaruh foot massage dengan aromatherapy oil terhadap kualitas tidur pada pasien yang menjalani hemodialisa. Penelitian ini adalah kuasi eksperimen dengan desain equivalent control group. Sample adalah 64 dipilih dengan menggunakan consecutive sampling. Data dikumpulkan dengan The Pittsburgh SleepQuality Index. Data dianalisis dengan pair t-test dan independent t-test. Hasil didapatkan ada perbedaan kualitas tidur pada kelompok intervensi setelah dilakukan tindakan (t=4,34, p=0,000) dan pada kelompok kontrol (t=3,31, p=0,002). Hasil juga menunjukkan bahwa ada perbedaan kualitas tidur antara kelompok tindakan dan kelompok kontrol pasien yang menjalani hemodialisa (t= 2,096, p=0,04). Kesimpulan ada pengaruh foot massage dengan aromatherapy oil terhadap kualitas tidur pada pasien yang menjalani hemodialisa. Saran tindakan foot massage dengan aromatherapy dapat menjadi salah satu tindakan non-farmakologi untuk membantu meningkatkan kualitas tidur pada pasien yang menjalani hemodialisa.